Trends in the treatment of undescended testes: a pediatric tertiary care center experience from Croatia - Marko Bašković; Davor Ježek; Ivona Sansovic; Luca Zaninović; Ana Maria Meašić; Ana Katušić Bojanac (BMJ Publishing Group, 2022)
Objective Undescended testes (UDT) is the most common anomaly of the male genitourinary tract. The guidelines suggest that orchidopexy in congenitally UDT should be performed between 6 months and 18 months of age, while in acquired UDT, orchidopexy should be performed before puberty. Delay in treatment increases the risk of cancer and infertility. The main aim of this study was to determine whether we meet international standards in the treatment of UDT.Methods The present study included all boys who underwent orchidopexy either due to congenital or acquired UDT in 2019 (from January 1 to December 31). For each group, laterality, location, associated anomalies, premature birth and in how many cases ultrasound was applied were determined. Additionally, for each group, the types of surgery, the number of necessary reoperations, and in how many cases atrophy occurred were determined. Finally, ages of referral, of clinical examination, and of orchidopexy were determined.Results During this period, 198 patients with 263 UDT underwent orchidopexy. The median time of orchidopexy for the congenital group was 30 months, while that for the acquired group was 99 months. In the congenital group up to 18 months of age, orchidopexy was performed in 16 (16%) boys, while in the acquired group up to 13 years of age, orchidopexy was performed in 95 (96.94%) boys.Conclusion Given the well-known risks of late treatment of UDT, orchidopexy needs to be performed much earlier, especially in the congenital group.